Determinan Akuntabilitas Kinerja pada Dinas Kelautan dan Perikanan Karangasem Bali - Aprilia, Arista; Susbiyani, Arik; Fitriah, Elok (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The process of exercising state power in carrying out the provision of public goods and services is part of good governance. The Government Agency Performance Report (LAKIP) is considered necessary to determine the ability of each agency to achieve the vision, mission, and objectives of the organization. Performance accountability is a form of performance reporting that must be accounted for by the party entrusted to carry out programs or activities in order to achieve the vision and mission and strategic plan that has been set by the organization. The type of data used in this study is subject data. In conducting this research, data collection techniques were used as follows: questionnaires (Questionnaires) namely distributing a list of questions in the form of questionnaires to respondents. The object of the research that I took was at the Karangasem Bali Marine and Fisheries Service. The results of this study based on several data analyses showed a positive and significant influence. This proves that the better the Budget Implementation will increase the accountability of the performance of the Karangasem Bali Marine and Fisheries Service.